Hybrids acceptance tools for the CMS Phase-2 Tracker Upgrade. (1st June 2022) - Hollos, A.; Blanchot, G.; Kovacs, M.; Loutit, M.; Makarenko, I.; Mateos, I.; Otarid, Y.; Seif El Nasr, S.; Zografos, A.; ,
Abstract: Up to fifty thousand front-end and service hybrids are required for the CMS Outer Tracker Phase-2 Upgrade. These hybrids, which are built on carbon fibre stiffened circuits and contain several flip-chip ASICs, will be glued in module structures, making repairs almost impossible. Due to their complexity, testing within production is a very important aspect. A multiplexed testing infrastructure, based on custom crates and test cards, is presented. This testing hardware is supported by software tools to enable the exhaustive verification of hybrids at the manufacturing sites and for their acceptance within the collaboration.